DOES GREEN COMPANY IMPROVE FINANCIAL PERFORMANCE? : EMPIRICAL STUDY ON MINING COMPANIES IN INDONESIA - Deddy Kurniawansyah; Indah Prastiwi (Berkala Akuntansi dan Keuangan Indonesia, 2022)
The purpose of this study is to examine the effect of environmental performance, ISO 14001, media disclosure on financial performance of mining companies in Indonesia. The population is mining companies listed on the Indonesia Stock Exchange in 2016-2021 of 247 annual reports. This study was use census method for the sampling technique. Data analysis techniques was use path analysis with SmartsPLS 3.0 software as tool. This study found that Environmental performance, media disclosure was effect on financial performance. While, ISO 14001 was not affected on financial performance. This study contribution is strengthening stakeholder theory and legitimacy as the basis of the accounting theory literature. Furthermore, as an earth friendly enterprise strategy tool for managers that significantly improves financial performance. The realization of the financial performance of mining companies that pay attention to environmental issues (green company) can contribute to strengthening the Indonesian economy and achieving the goals of sustainable development goals (SDGs).